The Experiment of Partial Discharge testing for Low Voltage Motor - Sawangsri, Jaturaphat; Wiangtong, Theerayod; Pathanrat, Khomsan; Ruangwong, Khomsan; Jeenmuang, Siwakorn; Pattanadech, Norasage (My University, 2025)
Low-voltage (LV) motors are widely used and highly popular in industrial settings due to their critical role in production processes. Any malfunction or failure of an LV motor can lead to production downtime, resulting in reduced output and potential revenue loss. Therefore, it is essential to conduct diagnostic assessments that evaluate the reliability of the insulation system in LV motors. Partial Discharge (PD) testing is recognized as a highly effective and reliable method for assessing the condition of motor insulation. This paper presents PD testing on LV motors to investigate the behavior of partial discharges using multiple analysis techniques. Additionally, an acoustic camera is integrated into the testing process to accurately identify the discharge locations.
Keywords: LV motor; partial discharge; PRPD pattern